ANALYSIS FINANCIAL REPORTS IN PREDICTING THE OCCURRENCE OF FRAUD WITH THE BENEISH M-SCORE MODEL IN MINING COMPANIES LISTED ON THE IDX IN 2021-2023 - Wulandari, Luh Putu Jesita; Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the potential for financial reporting fraud in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2023 using the Beneish M-Score model. This model is used to detect indications of financial reporting manipulation through the analysis of eight financial ratios that are processed into accumulative scores. Based on the results of the analysis, companies are grouped into three categories, namely manipulators, non-manipulators, and grey companies. The results showed that the number of companies classified as manipulators decreased significantly during the observation period, from 27.59% in 2021 to 6.90% in 2023. In contrast, the number of non-manipulators increased from 68.97% in 2021 to 86.21% in 2023. Meanwhile, grey companies experienced a slight increase, from 3.45% to 6.90%. These findings indicate that in general the integrity of financial reporting in mining companies has improved from year to year. This research is expected to provide relevant information for investors, creditors, and other interested parties in assessing the quality of the company's financial reports.